If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-(7x-3)=8-(x+9)
We move all terms to the left:
2x-(7x-3)-(8-(x+9))=0
We get rid of parentheses
2x-7x-(8-(x+9))+3=0
We calculate terms in parentheses: -(8-(x+9)), so:We add all the numbers together, and all the variables
8-(x+9)
determiningTheFunctionDomain -(x+9)+8
We get rid of parentheses
-x-9+8
We add all the numbers together, and all the variables
-1x-1
Back to the equation:
-(-1x-1)
-5x-(-1x-1)+3=0
We get rid of parentheses
-5x+1x+1+3=0
We add all the numbers together, and all the variables
-4x+4=0
We move all terms containing x to the left, all other terms to the right
-4x=-4
x=-4/-4
x=1
| x^2-19x+13=0 | | 4x-5×(x-1)=-2x+4 | | 12/14=18/x | | -4y-13=2y+17 | | -6=-3/8v | | 2(5^(2x-3))-4=7 | | 4n^2+31=-8n | | x3+7x^2-36=0 | | 5x-6=11x-48 | | 5^(2x-3)=(11/2) | | 7x-2x2=0 | | 5^(2x-3)=6 | | 2/3x108-3/4=9/12x108 | | 5^2x-3=6 | | 2.5x=1.1x+1200 | | F(x)=x2+4x+7 | | 3.5-0.04x=0.82 | | 3y+1/5=2y+7/3 | | x-17=(5/9)x | | 1/3x+5/6=x-1/2 | | 12x-4+42=17x+6 | | X*(x+5)=204 | | 7(b+3)=10b+9-3(b-4) | | -54=-6x+7(6x+18) | | -8y-10=2y+20 | | (2x-4)=(6x-6) | | 43p^2+156p-48=0 | | -3/4=5x | | -33=4x-3(x+15) | | 12+b4=24 | | -11=b-16 | | -14=k-3 |